Model Perlindungan Saksi Dan Korban Sebagai Justice Collaborator Dalam Perkara Tidak Pidana Korupsi “Tinjuan Analisis Undang-Undang Perlindungan Saksi Dan Koban” - Ahmad Rosidi; Syaifullah Syaifullah; Idris Sardi; Awaludin Awaludin (JATISWARA, 2023)
Law enforcement in Indonesia, especially in each region, is strongly influenced by culture and culture in social life, in cases of criminal acts of corruption in particular, the community has a very important role both as justice collaborators in disclosing the occurrence of an act of criminal acts of corruption, terrorism, narcotics, laundering money, human trafficking and other organized criminal acts. As we know, a justice collaborator is defined as a perpetrator of a particular crime, but not the main actor who admits his actions and is willing to be a witness in the judicial process, and can play an active role in the legal process as a witness. The problem approach used in this study is a normative research approach and an empirical research approach. The normative research approach is an approach that is carried out through a study of laws, regulations, theories, concepts, views, and aspects related to the issues discussed. In addition, the approach in this study is also supported by an empirical research approach, namely an approach through field research by conducting interviews with the public and legal practitioners, carried out in order to find out the reality in the form of research, opinions, attitudes, related to efforts and implementation of witness protection. criminal acts of corruption, terrorism, narcotics, money laundering, trafficking in persons and other organized criminal acts.